Antimicrobial susceptibility of Escherichia coli isolated from diabetic patients in Mogadishu, Somalia - Hassan, Shafie Abdulkadir; Ahmed, Yousif Mousa Alobaid; Hassan, Gallad Dahir (Frontiers in Microbiology, 2023)
Urinary tract infections (UTIs) are a major concern for diabetic patients due to the impact of diabetes on the urinary tract and immune system. Escherichia coli is the most common pathogen causing UTIs in diabetic patients and is known for its resistance. This study aimed to assess the antimicrobial susceptibility of Escherichia coli strains isolated from diabetic patients in Mogadishu, Somalia.This descriptive cross-sectional study was conducted at Ummah Hospital in Mogadishu, Somalia, from November 2021 to April 2022. Clean catch mid-stream urine specimens were collected from each participant and uropathogens were identified using standard techniques. The samples were cultured on CLED agar and antibiotic susceptibility patterns were determined using the Kirby-Bauer disc diffusion method. Data analysis was performed using SPSS version 20.The overall prevalence of uropathogens among diabetic patients was 236/350 (67.5%) with Escherichia coli being the most common organism. According to multivariate logistic regression, the results showed that Female diabetic patients had a significantly higher likelihood of developing UTIs compared to males (AOR = 2.5, 95% CI: 1.357-4.522, p = 0.003). The duration of diabetes, history of previous UTIs, and previous antibiotic use were also significantly associated with UTIs. All isolates were found to be resistant to Cefotaxime (100%). In addition, high resistance rates were observed with ofloxacin (91%), ciprofloxacin (77.8%), amikacin (60.9%), ceftriaxone (58.3%), and cefepime (51.8%). The most sensitive antibiotics were colistin and imipenem (99.6% and 88.6%, respectively), followed by gentamycin (70%).Conclusions: This study found a high prevalence of uropathogens and increased multi-drug resistance.Continuous surveillance is needed to monitor uropathogen prevalence and resistance rates, guiding treatment recommendations, rational prescription programs, and policy decisions.